Beggary in Law and Islam: A Call to amend the Law in Pakistan (Al-Qamar, 2023)
Begging in Pakistan is a complex issue with no easy solutions. However, the current approach of criminalizing begging is ineffective and counterproductive. This paper argues that the law on begging in Pakistan needs to be amended to take into account the socio-economic factors contributing to begging and to provide a more compassionate and holistic response to the problem. Poverty, unemployment, and crime rates are prevalent in Pakistan, with begging becoming a necessary option for survival, as five to twenty-five million beggars are found in the country. The laws on begging in Pakistan lack any criteria for distinguishing between professional beggars and those who beg for survival. These laws violate the fundamental rights to life, liberty, equality, and free speech. This paper calls for a deeper understanding of the social and economic factors contributing to begging and the need to amend the law, keeping in due regard to the injunctions of Islam. Rather than punishing beggars, we should focus on addressing the underlying causes of begging and providing beggars with the support they need to live dignified lives. It is high time to create laws that cater to the socio-economic circumstances of our society and to approach this issue with empathy and compassion.
Keywords: Begging; Vagrancy; Beggary; The Punjab Vagrancy Ordinance; 1958; Beggary in Islam